Production Machine Maintenance Analysis Using the Failure Mode And Analysis Method and Logic Tree Analysis d i P T Symgreen Gresik - Gatot Basuki HM (Journal of Applied Sciences, Management and Engineering Technology, 2022)
Maintenance of production machines is a production control to maintain the productivity of the production process. PT. Symgreen is a company that produces ice cream sticks. To achieve optimal results, regular machine maintenance is required. The occurrence of damage to the production machine experienced during the production process, in some damage to machine components, so that production results were reduced. The Failure Mode and Effect Analysis method is used to identify the failure mode and overcome the failure mode in every machine breakdown. To determine the failure mode category for the corrective steps that must be taken immediately and the direction of action that must be chosen to overcome the failure mode, LTA (Logic Tree analysis) is used. The results of the analysis showed that there were 4 machines and 2 types of damage based on the components of the production machine, namely the cutting machine the problem was in a broken bearing with RPN 144 in category B, rotary engine gear cracked RPN 125 category B, rotary engine spindle stuck RPN 125 category B, engine champering gear broke RPN 120 category B, printing machine gear cracked RPN 125 category C. P roposed repairs by performing regular maintenance on machine components, compiling work manuals on each machine.Keywords: Failure Mode, Production Machine, FMEA, LTA, RPN.